2006
DOI: 10.1007/s10528-006-9026-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships among Indigenous Sheep Populations in East Asia based on Five Informative Blood Protein and Nonprotein Polymorphisms

Abstract: The phylogenetic relationships among 23 local sheep breeds and varieties in East Asia were determined based on allele frequency data for five informative and polymorphic blood protein and nonprotein loci (transferrin, arylesterase, hemoglobin-beta, X-protein, and potassium transport) using electrophoresis and ion-densitometric techniques. Comparatively striking differences in the frequency distributions, especially of hemoglobin-beta and X-protein alleles, were seen between the northern population of the Khalk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…2). This observation is also supported by previous conclusion made from biochemical study5. The two distinct high-altitude sheep groups provided a great opportunity to compare the adaptive mechanism within domestic sheep.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…2). This observation is also supported by previous conclusion made from biochemical study5. The two distinct high-altitude sheep groups provided a great opportunity to compare the adaptive mechanism within domestic sheep.…”
Section: Discussionsupporting
confidence: 85%
“…Kage and Lampuchhre sheep are two lowland breeds, distributed in the areas below 1500 masl. An earlier phylogenetic studies using blood proteins showed that Bhyanglung, as well as Tibetan and Changthangi sheep were derived from the Tibetan sheep group, and Baruwal belongs to Himalayan group, while Kage and Lampuchhre are associated with Indian group5. However, no genome-wide analysis was performed to examine the intra- and/or inter-population genetic variability or to detect the selection signatures for the high-altitude adaptation among these four major Nepalese sheep.…”
mentioning
confidence: 99%
“…This difference is predictable because the northern sheep group has high heterozygosity compared with the southern sheep group. Such a great difference has resulted from the clustering analysis of blood protein and nonprotein polymorphisms in East Asian sheep (Tsunoda et al 2006). The polymorphisms at three PrP codons are of phylogenetic interest for us.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the decreased haematocrit values, lower blood viscosity and more availability of water associated with Hb B blood types compared to Hb A types. This is buttressed by the reports of Tsunoda et al (2006) that Hb A allele has a high affinity for oxygen and is important for survival in mountain areas at altitudes over 3000 m and Pieragostini et al (2006)…”
Section: Haemoglobinmentioning
confidence: 99%